2019
DOI: 10.1002/ldr.3345
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil phosphorus and its influencing factors following afforestation in Northern China

Abstract: Changes in soil carbon (C) and nitrogen (N) stocks following afforestation have been widely studied at different scales. However, soil phosphorus (P) dynamics following afforestation are poorly understood, especially at the regional scale. This paper studied the effects of prior land use (cropland, grassland, and barren land), tree species (conifer, broadleaf, shrub, and mixed), plantation age (young, middle, and old), and climate on soil total phosphorus and available phosphorus stocks change in the top 20 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
(108 reference statements)
2
21
0
Order By: Relevance
“…Interestingly, soil total phosphorus mediated the balance between stochastic and deterministic assembly processes for the abundant and rare bacteria, while the community assembly of abundant and rare bacteria had distinct response strategies to total phosphorus during successional reforestation. As a major nutritional constraint for primary production in terrestrial ecosystems (Cleveland et al, 2013), soil phosphorus content cannot be quickly replenished as it is primarily obtained from rock weathering (Walker and Adams, 1958;Li et al, 2019). And this further affects the dynamics of soil C stocks (Shi et al, 2016) and nitrogen cycling (Vitousek et al, 2010).…”
Section: Soil Phosphorus Drives Distinct Assembly Strategies For Abundant and Rare Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, soil total phosphorus mediated the balance between stochastic and deterministic assembly processes for the abundant and rare bacteria, while the community assembly of abundant and rare bacteria had distinct response strategies to total phosphorus during successional reforestation. As a major nutritional constraint for primary production in terrestrial ecosystems (Cleveland et al, 2013), soil phosphorus content cannot be quickly replenished as it is primarily obtained from rock weathering (Walker and Adams, 1958;Li et al, 2019). And this further affects the dynamics of soil C stocks (Shi et al, 2016) and nitrogen cycling (Vitousek et al, 2010).…”
Section: Soil Phosphorus Drives Distinct Assembly Strategies For Abundant and Rare Bacteriamentioning
confidence: 99%
“…And this further affects the dynamics of soil C stocks (Shi et al, 2016) and nitrogen cycling (Vitousek et al, 2010). In addition, soil P concentration in the Loess Plateau is lower on average than the global mean, which exacerbate soil P as the main limiting factor (Li et al, 2019). Previous research has shown that soil phosphorus significantly influenced the structure and diversity of the soil microbial community in Loess Plateau ecosystems (Jangid et al, 2013;Chen et al, 2014;Li et al, 2019;Randall et al, 2019).…”
Section: Soil Phosphorus Drives Distinct Assembly Strategies For Abundant and Rare Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these factors may be characterized by a few variables; for example, climate may be characterized by mean annual temperature (MAT) and precipitation (MAP). Relationships between soil total P concentration and variables such as parent material type and P concentration, MAT, MAP, site slope, and soil organic carbon (SOC) have been reported in previous studies but mostly at local to regional scales (Brédoire et al, 2016;Cheng et al, 2018;Li et al, 2019;Porder and Chadwick, 2009;Wang et al, 2009). Few studies have quantified the relative importance of these variables for predicting soil total P concentration at a global scale (Delgado-Baquerizo et al, 2020;Augusto et al, 2017;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [19] found that the contents of SOC, TN, AN, and AK in woodland were much higher than those in grassland, shrubland, and cropland, but land-use types did not significantly affect other soil nutrient contents (e.g., TP and TK); they also drew the conclusion that climate factors, soil texture, and pH induced the variations of soil nutrient contents. The conclusions of regional-scale studies might contrast with each other due to the difference in climate, geological background, and soil conditions [20], which highlights the significance of regional studies into different ecosystems. Different from natural soils, reclaimed soils are much more heterogeneous and compact due to the irregular mixing of different materials (e.g., plant residues, fly ash, and soil particles) and the compaction of it by heavy machinery [21,22].…”
Section: Introductionmentioning
confidence: 99%